Preserving the vitality of teeth adjacent to a large radicular cyst in periapical microsurgery: a case report with 4-year follow-up - Ahmed Elhakim; Sunil Kim; Euiseong Kim; Alaa H. Elshazli (BMC, 2021)
Abstract Background Radicular cysts may enlarge considerably, cause extensive bone destruction, and jeopardize the integrity of the associated vital teeth. The different treatment approaches are aimed mainly at eliminating the cystic epithelial membrane while reducing the risk of injury to vital structures. Contrary to other treatment modalities, preapical surgery offers an unequivocal single occasion resolution for the patient. However, it has been associated with higher risk of collateral damages. Case presentation A patient presented with a large radicular cyst originating from a maxillary lateral incisor. The adjacent central and canine teeth initially failed to exhibit responses to sensibility tests but showed signs of vitality. Microsurgical management was aimed at enucleating the cystic membrane while maintaining adjacent teeth vitality. Upon careful and controlled cyst enucleation under the dental operating microscope, the neurovascular bundle of one of the involved teeth was visualized and its integrity was maintained throughout the procedure. Results The procedure was successful and follow up recalls revealed recovery of normal sensibility of tooth 11 and 13 with complete bone regeneration around their apices. Conclusion Within the limitation of the present case report, we demonstrated that complete excision of large periapical cyst can be performed without sacrificing the vitality of the adjacent teeth, by preserving the integrity of their neurovascular supply through controlled microsurgical enucleation, and by a potential apical vascular repair ensuing unintended injury. Diagnosing the pulp vitality of non-offending teeth whose apices protrude into the cystic lumen is a complex process and can be misleading. Pressure from the growing cyst can inhibit vital teeth responses to neural-based sensibility tests leading to false negative results. Thus, in such cases, the use of blood perfusion-based vitality testing is recommended for correct initial diagnosis.